Analisis Pendapatan Usahatani dan Faktor Pendorong Serta Penghambat Pengelolaan Usahatani Kopi di Kabupaten Toba Samosir - Nainggolan, Hotden Leonardo (AGRIMOR, 2024)
The low use of farming technology, lack of knowledge of coffee farmers causes the productivity of this farming to be not optimal. This study aims to analyze the income of coffee farming and the factors driving and inhibiting the management of coffee farming in Districtc of Toba Samosir, which was carried out from January to April 2023. The data used were primary data and secondary data which were analyzed descriptively. The results showed; a) The average production cost of coffee farming is IDR3,385,056.00/year and the average income of farmers is IDR14,963,610.67/year/ha; b) The most dominant driving factors for coffee farming management are; coffee farming as a support source of family income and high motivation of farmers, c) The most dominant inhibiting factor in the management of coffee farming is the limited capital for farming and the lack of mastery of technology. In accordance with the results of the study suggested; a) So that farmers carry out optimal maintenance of their farms, b) So that local governments provide counseling to farmers, provide capital assistance and subsidies for fertilizers and medicines for farmers and provide technology training for farmers including the establishment of farming cooperatives.